Study on the Solid Phase Extraction of Co(II)-N,N’- Disalicylideneethylene diamine Chelate with C18 Disk and Its Application in Determination of Trace Cobalt - TAJODINI, NILOFAR; MOGHIMI, ALI (Asian Journal of Chemistry, 2010)
A sensitive, selective and rapid method has been developed for the determination μg L-1 level of cobalt based on the rapid reaction of cobalt(II) with N,N'-disalicylidene-ethylenediamine (NNDED) and the solid phase extraction (SPE) of the coloured chelate with Waters Porapak Sep-Park C18 disk. The N,N'-disalicylidene-ethylenediamine can reacts with Co(II) in the presence of pH 4.2, acetic acid-sodium acetate buffer solution and cetyl trimethylammonium bromide (CTMAB) medium to form a violet chelate of a molar ratio 1:2 (cobalt to NNDED. This chelate can retained on Waters Porapak Sep-Park C18 disk quantitatively when they passed the disk as aqueous solution. After the enrichment finished, the retained chelate can be eluted from disk by 2.5 mL of ethanol (contain 5 % acetic acid). In the measured solution, the molar absorptivity of the chelate is 1.58 × 105 L mol-1 cm-1 at 635 nm and Beer's law is obeyed in the range of 0.01-0.4 μg mL-1. The relative standard deviation for 11 replicate sample of 0.01 μg mL-1 level is 2.54 %. The detection limit is 0.01 μg mL-1 (in original samples). This method can be applied to the determination of μg mL-1 level of cobalt in drinking water with satisfactory results.